Adolescents’ drug poisoning profile during the Covid-19 pandemic in the southeast region of Serbia - Kostić, Emilija; Vujović, Maja; Milosavljević, Biljana; Simić, Jovana; Antović, Aleksandra; Milić, Miroslav; Pinterović, Bogdan; Pančić, Dimitrije; Miljković, Milica (Archives of Pharmacy, 2022)
During the Covid-19 pandemic, an increase in the number of poisonings was observed worldwide. Due to the lifestyle changes, adolescents were exposed to accidental and intentional poisoning. Epidemiological data on this important health issue are scarce in southeast Serbia, so the need for a current review of drug intoxication patterns in this population is imperative, in order to prevent more intoxications. The cross-sectional retrospective study was conducted in Niš, southeast Serbia, which resides a population of nearly 2 million inhabitants. The data were extracted from records available at the Institute of Forensic Medicine in Niš from March 2020 to March 2022. The cases were reviewed for gender, age and drugs identified by toxicological analyses. Results were statistically analyzed using SPSS 2020. The highest prevalence of 25% (80 cases) of recorded intoxications caused by drugs (320) among general population, was observed in adolescent group (age 12-19). This is a significant increase compared to the results of Military Medical Academy Belgrade assessment for 2018 (9.7% of intoxication in minors). The statistical predominance of intoxication was observed in females (75%). Combined drug poisoning was reported in 50% of cases. Benzodiazepines (45.24%) were identified in the largest number of cases (bromazepam and diazepam predominantly), followed by analgesics (21.43%), antiepileptics (15.87%) and antidepressants (7.93%). The number of poisoning cases in the adolescent population is alarming and points to the large influence of pandemics on mental health, especially in female adolescents. These results emphasize the need for action in mental care and prevention.